Metal Nanoparticles in Atherosclerosis: Applications and Potential Toxicity - Fatemeh Imanparast; Mahmood Doosti; Mohammad Ali Faramarzi (Nano Biomedicine and Engineering, 2015)
As a chronic inflammatory disease, atherosclerosis is responsible for thousands of deaths worldwide each year, and it imposes massive economic costs on individuals and on society. Because of its high importance, the discovery of sensitive and accurate strategies for imaging, targeted drug delivery, and therapeutic monitoring of this condition is essential. In recent years, continuous research has achieved remarkable successes in the use of nanotechnology in the molecular imaging and treatment of atherosclerosis. Among various nanoparticles — such as metallic, polymeric, and lipid — metallic nanoparticles are being considered due to their unique properties for use in treatment and imaging. It should be taken into consideration that some of the metal nanoparticles themselves can cause adverse biological effects, and these effects should be considered important risk factors in the pathological pathways leading up to atherosclerosis. This review provides a description of the applications and potential toxicity of metal nanoparticles in atherosclerosis.